An Influence of Normal Stress and Pore Pressure on the Conditions and Dynamics of Shear Crack Propagation in Brittle Solids; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Shilko E. V. Evgeny Viktorovich (2016, 2016)
Title screen